2017
DOI: 10.15761/tim.1000108
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and antibiotic susceptibility pattern of urinary tract infection isolated from asymptomatic and symptomatic diabetic patients attending tertiary hospital in Jos, Nigeria

Abstract: Urinary tract infection (UTI) is an infection caused by the presence and growth of microorganisms in the urinary tract. In most cases empirical antimicrobial treatment is usually initiated before the laboratory results are made available; hence the need for antibiotic susceptibility test to enhance management of UTI. The study was designed to determine the bacterial profile and antibiotic susceptibility pattern of urinary tract bacteria isolated from symptomatic and asymptomatic diabetic patients at Bingham Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 13 publications
4
17
2
Order By: Relevance
“…Treatment of nosocomial infections is becoming a challenge as a result of resistance to antibiotics and the associated burden (Cao et al, 2014). Klebsiella pneumoniae, Staphylococcus aureus, Escherichia coli, Proteus spp, Pseudomonas spp., and other isolated bacteria have been implicated as contributing agents of nosocomial infections, and were also reported in the study by Kibret and Abera (2014), Derese et al (2016), andAnejo-Okopi et al (2015). The Klebsiella pneumoniae obtained in the study though had the highest incidence of occurrence when compared with other isolates at 33% was still low generally which aligns with other studies where the occurrence was reported to be low (Farajnia et al, 2009;Kamrul et al, 2012).…”
Section: Discussionsupporting
confidence: 88%
“…Treatment of nosocomial infections is becoming a challenge as a result of resistance to antibiotics and the associated burden (Cao et al, 2014). Klebsiella pneumoniae, Staphylococcus aureus, Escherichia coli, Proteus spp, Pseudomonas spp., and other isolated bacteria have been implicated as contributing agents of nosocomial infections, and were also reported in the study by Kibret and Abera (2014), Derese et al (2016), andAnejo-Okopi et al (2015). The Klebsiella pneumoniae obtained in the study though had the highest incidence of occurrence when compared with other isolates at 33% was still low generally which aligns with other studies where the occurrence was reported to be low (Farajnia et al, 2009;Kamrul et al, 2012).…”
Section: Discussionsupporting
confidence: 88%
“…36 On the other hand, coagulase negative staphylococci was the third most common species identified in the present study whereas it was the predominant one in a study conducted in Nigeria. 12 Gram-positive cocci play a lesser role in causing UTI. Among the patients infected with Gram-positive cocci in our study, CoNS, 7 (17.9%), was the predominant isolate, followed by S. aureus, 3 (7.7%).…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18] Several uropathogens have been identified in diabetic patients and the most common uropathogens isolated are Escherichia coli, Klebsiella spp., and Staphylococcus aureus. 7,9,12,18 Due to different reasons, these bacterial uropathogens showed wide-ranging resistances to different classes of antibiotics across the world. 6,7, In diabetic patients, early diagnosis of UTI is essential for its proper management and to avoid the incidence of possible complications.…”
Section: Introductionmentioning
confidence: 99%
“…7 E. coli (19.2%), CNS (46.15%), K. pneumoniae (19.23%), S. aureus (3.84%), and Streptococcus spp. (11.53%) while that of the asymptomatic was; E. coli (31.25%), CNS (18.75%), S. aureus (31.35%), and Streptococcus spp.…”
Section: Discussionmentioning
confidence: 99%